Internet censorship detected in Myanmar (Myanmar) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Myanmar. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0334. Severity: warning. Confidence: 65%